Cycled bobsleigh basics training system for 13-14 year-old beginners - Maslov, I. S.; Kudryavtsev, M. D.; Arutyunyan, T. G.; Zakharova, L. V.; Shivit Huurak, I. K. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to offer and test benefits of a cycled bobsleigh basics training system for the 13-14 year-old first-year trainees with a special emphasis on physical fitness.